Detection of MDM2 amplification by shallow whole genome sequencing of cell-free DNA of patients with dedifferentiated liposarcoma. - Joanna Przybyl; Lien Spans; Kristen Ganjoo; Nam Bui; David Mohler; Jeffrey Norton; George Poultsides; Maria Debiec-Rychter; Matt van de Rijn (PLoS ONE)
High-level amplification of MDM2 and other genes in the 12q13-15 locus is a hallmark genetic feature of well-differentiated and dedifferentiated liposarcomas (WDLPS and DDLPS, respectively). Detection of this genomic aberration in plasma cell-free DNA may be a clinically useful assay for non-invasive distinction between these liposarcomas and other retroperitoneal tumors in differential diagnosis, and might be useful for the early detection of disease recurrence. In this study, we performed shallow whole genome sequencing of cell-free DNA extracted from 10 plasma samples from 3 patients with DDLPS and 1 patient with WDLPS. In addition, we studied 31 plasma samples from 11 patients with other types of soft tissue tumors. We detected MDM2 amplification in cell-free DNA of 2 of 3 patients with DDLPS. By applying a genome-wide approach to the analysis of cell-free DNA, we also detected amplification of other genes that are known to be recurrently affected in DDLPS. Based on the analysis of one patient with DDLPS with longitudinal plasma samples available, we show that tracking MDM2 amplification in cell-free DNA may be potentially useful for evaluation of response to treatment. The patient with WDLPS and patients with other soft tissue tumors in differential diagnosis were negative for the MDM2 amplification in cell-free DNA. In summary, we demonstrate the feasibility of detecting amplification of MDM2 and other DDLPS-associated genes in plasma cell-free DNA using technology that is already routinely applied for other clinical indications. Our results may have clinical implications for improved diagnosis and surveillance of patients with retroperitoneal tumors.